TERRITORIAL PECULIARITIES OF DIFFIRENTIAL ASSESSMENT OF PHYSICAL FITNESS OF RURAL SCHOOLCHILDREN - Ubaydullaev Rahimjan (Journals Park Publishing, 2022)
In addition, the kundalik life support of a person meets the requirements of various groups for building muscle mass.
Keywords: impulslar, biologik, organlar, chaqqolik.